ANALISIS PENGGUNAAN CDI STANDAR DAN CDI RACING DENGAN VARIASI BAHAN BAKAR PERTALITE, PERTAMAX 92 DAN PERTAMAX 98 TERHADAP DAYA DAN TORSI MOTOR BENSIN 1 SILINDER - Rizky Yusuf Efendi; Nurcholis Arifin Handoyono; Samsul Hadi (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to determine the comparison of the power and torque produced by motorcycle engines using standard CDI and CDI racing BRT with variations in pertalite, Pertamax 92, and Pertamax 98 fuels. The type of research used is descriptive quantitative. Data collection techniques using tests, namely by testing the object under study then measuring and recording directly the resulting data. The testing process uses the help of a dynamometer measuring instrument. Data collection was carried out at 6000 to 11000 rpm rotation. The results showed that the power and torque produced using standard CDI DC on pertalite fuel showed the lowest value with a maximum power of 22.5 HP at 9168 rpm and a maximum torque of 19.78 Nm at 6576 rpm, on Pertamax 92 fuel the maximum power was 22, 6 Hp at 8370 rpm, with a maximum torque of 19.99 Nm at 7246 rpm and the Pertamax 98 fuel shows the highest value with a maximum power of 23.2 Hp at 8931 rpm and a maximum torque of 20.16 Nm at 7345 rpm. For the power and torque generated by the use of CDI DC racing BRT on pertalite fuel, it shows the lowest value with a maximum power of 22.9 Hp at 8604 rpm and a maximum torque of 19.43 Nm at 7670 rpm, on Pertamax 92 fuel the maximum power is 23, 6 Hp at 8979 rpm, with a maximum torque of 19.81 Nm at 7552 rpm and the Pertamax 98 fuel shows the highest value with a maximum power of 23.8 Hp at 9156 rpm and a maximum torque of 20.36 Nm at 7458 rpm. The use of CDI DC racing BRT is able to serve engine performance at higher rpm rotations and produce greater power and torque for each type of fuel variation.